Design and prototypical implementation of a mobile healthcare application : health express - Shawkat, Shahan; Nasrullah, Musa; Islam, Rahenul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2015.